Clinical Comorbidities and Videourodynamic Characteristics of Dysfunctional Voiding in Women - Cheng-Ling Lee; Yuan-Hong Jiang; Jia-Fong Jhang; Tien-Lin Chang; Jing-Hui Tian; Hann-Chorng Kuo (Biomedicines)
Purpose: The current study aimed to investigate the clinical comorbidities and urodynamic characteristics of a large cohort of women with dysfunctional voiding (DV) validated on a videourodynamic study (VUDS). Methods: Women who presented with VUDS-confirmed DV from 1998 to 2022 were retrospectively analyzed. Data on clinical symptoms, VUDS findings, and medical comorbidities including medical illness and previous surgical history were recorded and examined. Patients with DV were subgrouped according to age, presence of medical comorbidity, and different urodynamic parameters. The urodynamic parameters and treatment outcomes among the different subgroups were examined. Results: In total, 216 women were retrospectively analyzed. Among them, 188 (88.3%) presented with storage symptoms and 130 (61.0%) with voiding symptoms. Regarding outcomes, 48 (22.2%) patients had successful treatment outcomes; 76 (35.2%), improved outcomes; and 92 (42.6%), failed outcomes. Then, 150 (69.0%) patients presented with urodynamic DO. Patients with terminal DO experienced a significantly higher incidence of hypertension (56.8%), diabetes mellitus (37.9%), and latent central nervous system diseases (38.9%) than those with non-DO or phasic DO. Patients with phasic DO had a significantly higher detrusor pressure (Pdet) and bladder outlet obstruction index than those with non-DO and terminal DO. Patients with hypertension or those with a Pdet ≥ 35 cmH2O had high rates of successful treatment outcomes. Conclusions: DV is significantly associated with older age and a higher incidence of central nervous system diseases, hypertension, and diabetes mellitus in women. Patients with phasic DO had a high Pdet and BOO, and patients with hypertension or those with Pdet ≥35 cm H2O who received urethral sphincter treatment had a better treatment outcome.